Pengaruh Substitusi Tepung Kulit Pisang Raja Terhadap Kadar Serat dan Daya Terima Cookies - Kahara, Dina Gati; , Pramudya Kurnia, STP, M.Agr; , Endang Nur W., SST., M.Si. Med (2016)
Introduction: Banana (Musa parasidiaca) peel has a high content of crude fiber and can be processed into cookies. Banana peel flour can be used as an ingredient in the making of cookies to increase fiber content. The use of banana peel flour and can affect the chemical quality, physical quality and sensory quality cookies. Purpose: The purpose on this study was to determine effect of banana peel flour stitution fiber content and acceptability of cookies. Methods: The design of this study was completely randomized design with 4 treatments that is banana peel flour substitution is 0% (control), 10%, 20% and 30%. Levels of fiber content were tested using the method of Gravimetry and acceptability of cookies using organoleptic test by seven levels of hedonic scale. Both data of fiber content and acceptability are not homogeneous and not normal so that Kruskal Wallis test was implemented. Results: The results showed that there was no substitution effect on the fiber content cookies. There was a significant substitution on acceptability of color, aroma, flavor, texture and overall cookies, with significant value respectively p=0,000; p=0,017; p=0,000; p=0,017; dan p=0,000. Conclusions: The highest fiber content (2,94%) contained in cookies with the substitution of 30%. Based on a acceptability it is recommended to use of 10% banana peel flour 10%. Keywords: cookies, banana peel flour, fiber content, acceptability